Relationship between cardiorespiratory fitness and body fatness with cardiovascular disease risk factors - Foo, Phildia Qizhen (2014)
The prevalence of cardiovascular disease (CVD) is increasing but there is limited information on the relationship between cardiorespiratory fitness and body fatness with CVD risk factors,